The Impact of Social Restriction Policies During the COVID-19 Pandemic on the Crew Change Process at PT Tanjung Perdana Cemerlang - Derma Watty Sihombing; Mukhlas Hamdani; Rosmayana Rosmayana; Ronald Simanjuntak; Arya Maula Nurhidayat; Triyul Bagus Bangun Pekertri (Meteor STIP Marunda, 2023)
This study examines how social restriction policies during the COVID-19 pandemic affected the crew rotation process at PT. Tanjung Perdana Cemerlang, a maritime crew recruitment and placement company. The research uses a qualitative approach with data collected through observation, documentation review, interviews, and literature study during a twelve-month internship from August 2021 to August 2022. SWOT analysis was applied to evaluate the company's internal and external factors in managing crew changes during the pandemic. The findings show that crew rotation declined by 45.63%, dropping from an average of 17 crew changes per month in 2019 to only 9 per month in 2020, as PSBB and PPKM policies restricted crew mobility across Indonesia. The SWOT analysis indicates that the company should adopt a combination of turn-around and aggressive strategies, using its hospital partnerships, pharmaceutical supplier networks, and Compas software to offset weaknesses in health protocol enforcement and crew transparency. The study concludes that reducing sailing contract durations and enforcing strict pre-boarding health protocols would improve crew rotation efficiency during pandemic conditions.